Design and Test of an Antenna Module Mock-Up for the EAST 4.6 GHz LHCD Launcher - 贾华 刘甫坤 刘亮 程敏 赵连敏 王晓洁 章家方 (Plasma science & technology, 2013)
The launcher of the 4.6 GHz lower hybrid current drive （LHCD） system for the Experimental Advanced Superconducting Tokamak （EAST） consists of 24 antenna modules, each composed of an array of 3 （row） × 8 （column） waveguides. In order to verify the radio frequency （RF） design and the feasibility of the manufacturing process, a mock-up of the module has been fabricated and measured. The measured return losses of all three input waveguides are less than 25 dB at a frequency of 4.6 GHz. The transmission coefficients from the input waveguide to the output waveguides are 9.13 ± 0.2 dB and the insertion loss is 0.104 dB. These good results mean that the design method of the antenna module can be used for the new 4.6 GHz launcher on EAST. The detailed design of the multi-junction antenna module and its initial test result are described in this paper.